2020
DOI: 10.1097/ico.0000000000002256
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Light Scatter After Ultrathin Descemet Stripping Automated Endothelial Keratoplasty Versus Descemet Membrane Endothelial Keratoplasty in Descemet Endothelial Thickness Comparison Trial: A Randomized Controlled Trial

Abstract: Purpose: To compare the degree of corneal light scatter as measured by densitometry in ultrathin Descemet Stripping Automated Endothelial Keratoplasty (UT-DSAEK) and Descemet Membrane Endothelial Keratoplasty (DMEK) in the Descemet endothelial thickness comparison trial. Methods: This was a prespecified secondary analysis of the Descemet endothelial thickness comparison trial, which was a prospective, randomized controlled trial. Subjects with isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…They reported that the posterior corneal surface had significantly less coma and total HOA in DMEK compared to ultrathin DSAEK as well as less posterior trefoil, secondary astigmatism and tetrafoil. Finally, Hirabayashi and colleagues 46 measured corneal light scatter between UT-DSAEK and DMEK and found no difference in the Pentacam densitometry between the two groups at 3,6 and 12 months with both procedures improving after the procedures. They felt that the HOA in the posterior cornea were responsible for any differences between the two procedures rather than the stromal-stromal interface haze.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the posterior corneal surface had significantly less coma and total HOA in DMEK compared to ultrathin DSAEK as well as less posterior trefoil, secondary astigmatism and tetrafoil. Finally, Hirabayashi and colleagues 46 measured corneal light scatter between UT-DSAEK and DMEK and found no difference in the Pentacam densitometry between the two groups at 3,6 and 12 months with both procedures improving after the procedures. They felt that the HOA in the posterior cornea were responsible for any differences between the two procedures rather than the stromal-stromal interface haze.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Torras-Sanvicens et al did not observe statistically significant differences in total, anterior or posterior HOAs 12 months after surgery [ 6 ], which is in line with the results of other groups [ 19 ]. Altogether, it should be highlighted that the published data differ in terms of the operating techniques, corneal topographer device, definitions of UT-DSAEK grafts below 100 μm [ 8 , 9 , 20 ] or below 130 μm [ 3 , 7 ] and selection of study groups used, which makes it impossible to draw definite conclusions. It is worth mentioning that none of the previous studies compared the postoperative corneal curvature and topography parameters with their baseline values recorded preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate densitometry values for the central 0 to 6 mm optical zone, the 0 to 2-mm and 2 to 6-mm zones were combined using the methods previously described by Hirabayashi et al. 29 …”
Section: Methodsmentioning
confidence: 99%